KAJIAN JUMLAH SEL TERLEPAS DAN KARAKTER CARRIER PADA BERBAGAI KONSENTRASI TEPUNG PEPAYA DAN LAMA PENYIMPANAN SEL TERIMOBIL DALAM BEADS - Christiane, Claudia; Widyastuti, Theresia Endang Widoeri; Kuswardhani, Indah (Jurnal Teknologi Pangan dan Gizi, 2016)
Papaya flour added as prebiotic can influencing the cell growth (Lactobacillus acidophilus FNCC 0051) and beads texture, also total released cells from the beads thus affecting carrier characteristic. The purpose of this research is to study the interaction of papaya flour concentration and storage time, also effect of each factor to total released cells and carrier characteristic. The research design used is Factorial Randomized Block Design (RBD) with two factors namely concentration of papaya flour consisting of two levels, which were 3% (w/v) and 6% (w/v) and the storage time consisting of five (5) levels, which were 0, 7, 14, 21, and 28 days. Each treatment combinations are repeated three times. The analyzed variables were total released cells, pH, total acidity from milk as carrier and also the total of immobilised cells. Data analyzed statistically using ANOVA test (Analysis of Varians) at α = 5% and continued with DMRT (Duncan's Multiple Range Test) at α = 5% to determine which level of treatment that gives significant differences. Papaya flour concentration and storage time give significant interaction effect to the total released cells and total acidity, also significant effect of each factor to carrier’s pH. The higher concentration of papaya flour and the longer storage time increased the total released cells and total acidity. The significant increase of total acidity found in combination of various concentration of papaya flour with 14 to 28 days of storage. The higher concentration of papaya flour or the longer storage time decreased the pH value.